Pengaruh Digital Perbankan, Motivasi, Pelatihan dan Kepemimpinan terhadap Kinerja Karyawan pada PT Bank Central Asia Cabang Batam - Astarizal, Astarizal; Ngaliman, Ngaliman; Windayati, Diana Titik (Zona Manajerial: Program Studi Manajemen (S1), 2021)
This study aims to determine the factors that affect the dependent variable Y (employee performance). While the independent variables are X1 (digital banking), X2 (motivation), X3 (training) and X4 (leadership) at PT. Bank Central Asia Batam Branch. The population is all employees of PT Bank Central Asia Batam Branch as many as 135 employees. The sample was taken using the slovin formula with an e value of 5% so that the sample processed in the study was 100 employees. The data analysis technique is processed using the Statistical Product and Service Solution (SPSS) version 25 program application. The results of data analysis resulted in a multiple linear regression equation Y=11.529+0.247X1+0.464X2 - 0.010X3+0.147X4+e. Partial to each independent variable is digital banking of 0.168 > 0.05, motivation of 0.000 < 0.05, training of 0.933 > 0.05 and leadership of 0.181 > 0.05. The results of the partial regression analysis show that the digital variables of banking, training and leadership have a positive and insignificant influence on employee performance while motivation has a positive and significant influence on employee performance. The variables X1(digital banking), X2(motivation), X3(training) and X4(leadership) together contribute to a positive and significant influence on Y (employee performance) by a degree of signification (Sig F) 0.000 on employee performance < 0.05.